Characterization Of Machining Defects In Wood Planing Operation - Farrokhpayam, Saeid Reza (2010)

(untitled)
The objective of this study was to evaluate the effect of some machining factors on the machinability of selected Malaysian hardwoods and to quantify the major types of machining defects in the planing operation. The study aims to reveal the relationship between the types of surface defects generated after planing with the variable factors. It also studies the sanding process as an indicator to reveal loss thickness (yield) after the planing process on defective planks. For this research, three wood species, Rubberwood (Hevea brasiliensis), Melunak (Pentace spp) and Dark Red Meranti (Shorea spp) were chosen based on their machining characteristics, commercial position in the local and global market, and their usage as a solid material in the furniture industry. 50 clear samples of each wood species, for each treatment, in a uniform moisture content (10%), of the final size of 19 by 102 × 910 mm, were machined by a planer unit, Weinig Unimat 23E using only the bottom spindle of the machine. The cutterhead had 4 knives with a diameter 120 mm, rotating at 6000 revolutions per minute (RPM). The depth of cut (0.8, 1.6 and 2.4 mm) and feed rate (8, 12 and 16 m/min) were the experimental variables, while all other factors were kept constant. The surface quality of the individual sample was examined both visually, and sense of tactile to classify the samples into five grades based on the amount and severity of defects present, as given in the standard (ASTM, D 1666 – 87). In every instance, 60 percent or more of the samples were defect-free, and the slightly defective pieces outnumber the more seriously defective ones, by a wide margin. An in-depth analysis of the samples surfaces, machined under the three parameters of processing, found that among these three factors, depth of cut had the most significant effect on torn and fuzzy grain. This research also revealed that the combination of feed rate, depth of cut and wood species used had no significant effect on the surface quality of samples. This research showed that the planing operation as a part of wood products manufacturing can influence the quantity or volume of product parts manufactured from a given amount of lumber and labor by affecting the processing yield. The proper machining factors in relation to the wood species used decreases the surface defects. These defects results in increasing labor cost, machining cost and loss of wood material. Therefore, the optimal condition for planing operation of the three Malaysian woods to produce the best yield was realized at the minimum of depth of cut, and maximum cutting marks number per millimetre.